Analisis Filosofis terhadap Komunikasi Organisasi dalam Pendidikan - Siregar, Awaluddinsyah; Nasution, Sonya Liani; Fauzi, Muhammad Armawi; Mesiono, Mesiono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Philosophical analysis of communication in education involves deep reflection on the nature, sources of knowledge, and ethical values in communicative interactions. The research aims to explore the essence of communication in supporting educational goals, both in the development of students' character and in transmitting knowledge. From the quote, there is an explanation of the type of research used, namely library research. This research is carried out by accumulating information from various sources, such as books, journals, theses, dissertations, and the internet. Before analyzing the literature, the researcher must clearly understand where the objective data will be obtained. This study found that communication in organizational and philosophical education is significantly interconnected. They are involved in the delivery of information, knowledge, and values in an environment